The activities of the internal affairs bodies in the 70s of the 20th century in order to ensure order in the society (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In 1970, a number of works were carried out to provide the internal affairs bodies with highly qualified and leaders, and the operation of a number of educational institutions at the level of the union affects the increase of experience and qualified personnel in police bodies. a very difficult situation has come. The article talks about the activities of the internal affairs body in maintaining peace in the society.